Oral and general health indicators for lebanese elderly in oral surveys: review article - Nada EL OSTA; Stéphanie TUBERT-JEANNIN; Nada BOU-ABBOUD NAAMAN; Martine HENNEQUIN; Lana EL OSTA; Negib GEAHCHAN (International Arab Journal of Dentistry (IAJD), 2012)
Various factors are taken into account in assessing objectively the dental status and the quality of life related to oral health, particularly in elderly. Basic socio-demographic characteristics and oral hygiene habits must be identified and screened, respectively. The dental health can be evaluated using indicators such as the ASA score or by determining the person’s level of autonomy. Cognitive ability of older people must be checked prior to use oral health questionnaires. This competence can be assessed by the Mini Mental State score (MMS). The use of Mini Nutritional Assessment (MNA) evaluates the nutritional status of patients. The aim of the article is to identify the most relevant indicators that can be used in epidemiological studies to assess the oral health of Lebanese elderly.